PENDUGAAN CADANGAN KARBON PADA TEGAKAN AGROFORESTRI (STUDI KASUS DI DESA PARBABA DOLOK - Lambok M. Siallagan; Rahmawaty Rahmawaty; Abdul Rauf (Peronema Forestry Science Journal, 2015)
Changes in landuse and land cover change through forest conversion is the caused of global warming. Due to the climate change, agroforestry systems is estimated to have a high potential for carbon sequestration in the atmosphere. Agroforestry systems contribute to reducing the increase in atmospheric CO2 and other greenhouse gases by increasing carbon in the soil and reduce the pressure for forest clearing, where the carbon comes from CO2 is taken up by plants and stored in the form of biomass. This study aimed to quantified the carbon content and to maped the distribution of carbon in agroforestry stands in Parbaba Dolok Village using data of remote sensing. Calculation of carbon stocks used non-destructive (allometric method).  Vegetation types that exist in distribution of land agroforestry in Parbaba Dolok Village are kopi, coklat, pinus, nangka dan durian. The amount of carbon stocks in agroforestry stands in Parbaba Dolok Village was 337,461 ton/ha. Differences in carbon content acquistion in this area was influenced by vegetation density, diversity of size, and distribution of vegetation density.Keywords: Agroforestry, Carbon Stock, Biomass